Respuesta :
All we have to do is get y alone and input our values to see if it makes the statement true.
y - 1 = 3(x + 2)
Add 1 to both sides.
y = 3x + 7
y = 3(1) + 7
y = 3 + 7
y = 10
FALSE
y - 2 = 3(x + 1)
Add 2 to both sides.
y = 3x + 3
y = 3(1) + 3
y = 3 + 3
y = 6
FALSE
y + 1 = 3(x - 2)
Subtract 1 from both sides.
y = 3x - 7
y = 3(1) - 7
y = 3 - 7
y = -4
FALSE
y + 2 = 3(x - 1)
Subtract 2 from both sides.
y = 3x -5
y = 3(1) - 5
y = 3 - 5
y = -2
TRUE
The only equation that makes this statement true is D, y + 2 = 3(x - 1).
y - 1 = 3(x + 2)
Add 1 to both sides.
y = 3x + 7
y = 3(1) + 7
y = 3 + 7
y = 10
FALSE
y - 2 = 3(x + 1)
Add 2 to both sides.
y = 3x + 3
y = 3(1) + 3
y = 3 + 3
y = 6
FALSE
y + 1 = 3(x - 2)
Subtract 1 from both sides.
y = 3x - 7
y = 3(1) - 7
y = 3 - 7
y = -4
FALSE
y + 2 = 3(x - 1)
Subtract 2 from both sides.
y = 3x -5
y = 3(1) - 5
y = 3 - 5
y = -2
TRUE
The only equation that makes this statement true is D, y + 2 = 3(x - 1).